2012
DOI: 10.1093/bja/aes210
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the cuff pressure on the swallowing reflex in tracheostomized intensive care unit patients

Abstract: We demonstrated that LaT, EMGp, and ALA of the swallowing reflex were influenced by tracheostomy tube CP. The swallowing reflex was progressively more difficult to elicit with increasing CP and when activated, the resulting motor swallowing activity and efficiency at elevating the larynx were depressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 17 publications
1
44
0
5
Order By: Relevance
“…Of the 10 accepted articles (Table 1), all were prospective case series [39][40][41][42][43][44][45][46][47]. Study sample sizes ranged from 11 [40] to 40 [42] patients and included heterogeneous diagnoses in all but two studies [41,45].…”
Section: Study Characteristics and Methodological Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 10 accepted articles (Table 1), all were prospective case series [39][40][41][42][43][44][45][46][47]. Study sample sizes ranged from 11 [40] to 40 [42] patients and included heterogeneous diagnoses in all but two studies [41,45].…”
Section: Study Characteristics and Methodological Quality Assessmentmentioning
confidence: 99%
“…Of the 10 accepted articles (Table 1), all were prospective case series [39][40][41][42][43][44][45][46][47]. Study sample sizes ranged from 11 [40] to 40 [42] patients and included heterogeneous diagnoses in all but two studies [41,45]. Nine of the included studies [39][40][41][42][43][44][45][46]48] were published in English and one was published in Japanese [47].…”
Section: Study Characteristics and Methodological Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while increasing cuff pressures have been shown to impact swallowing reflexes, subsequent impact on airway protection was not examined or reported (Amathieu et al . ). Furthermore, while some research has suggested aspiration risk to be greater when swallowing with a tracheostomy cuff inflated compared with deflated (Davis et al .…”
Section: Introductionmentioning
confidence: 97%
“…Whilst methodological differences (i.e., underlying aetiologies, clinical populations, sample sizes, tracheostomy conditions, research design) limit firm conclusions, evidence suggests that while swallowing biomechanics may be altered by changing tracheostomy conditions, there is no change in function. For example, while increasing cuff pressures have been shown to impact swallowing reflexes, subsequent impact on airway protection was not examined or reported (Amathieu et al 2012). Furthermore, while some research has suggested aspiration risk to be greater when swallowing with a tracheostomy cuff inflated compared with deflated (Davis et al 2002, Ding andLogemann 2005), these studies had methodological limitations.…”
Section: Introductionmentioning
confidence: 99%